Intravascular Near-Infrared Spectroscopy: A Possible Tool for Optimizing the Management of Carotid Artery Disease - Horváth, Martin; Hájek, Petr; Štěchovský, Cyril; Honěk, Jakub; Veselka, Josef (International Journal of Angiology, 2015)
Stroke is the second most common cause of morbidity and mortality in the Western nations. It is estimated that approximately one-fifth of all strokes or transient ischemic attacks are caused by carotid artery disease. Thus, treatment of carotid artery disease as a mean of stroke prevention is extremely important. Since the introduction of carotid endarterectomy, debate has persisted over the treatment strategy for carotid artery disease. Current recommendations have many potential flaws because they are often based on older trials performed before the introduction of modern pharmacotherapy and are mostly based on the angiographic degree of stenosis, without an emphasis on the pathophysiology of the disease. Most carotid events are caused by rupture or distal embolization of the content of an unstable atherosclerotic plaque with a large lipid pool. Thus, it is plausible that the information regarding the composition of the atherosclerotic plaque could play an important role in deciding on a treatment strategy. In this review article, we provide information about near-infrared spectroscopy, a new invasive imaging modality, which seems to be capable of providing such information.
Keywords: near-infrared spectroscopy; intravascular ultrasound; carotid artery stenting